Effects of endurance training on the expression of host proteins involved in SARS-CoV-2 cell entry in C57BL/6J mouse - Tamura, Y.; Jee, E.; Kouzaki, K.; Kotani, T.; Nakazato, K. (Physiological Reports, 2021)
The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is threatening people's lives and impacting their health. It is still unclear whether people engaged in physical activity are at an increased risk of SARS-CoV-2 infection and severe forms of COVID-19. In order to provide data to help answer this question, we, therefore, investigated the effects of endurance training on the levels of host proteins involved in SARS-CoV-2 infection in mice. Eight-week-old C57BL/6J mice were subjected to treadmill running (17-25 m/min, 60-90 min, 5 sessions/week, 8 weeks). After the intervention, the levels of angiotensin-converting enzyme 2 (ACE2; host receptor for SARS-CoV-2), transmembrane protease serine 2 (TMPRSS2; host protease priming fusion of SARS-CoV-2 to host cell membranes), FURIN (host protease that promotes binding of SARS-CoV-2 to host receptors), and Neuropilin-1 (host coreceptor for SARS-CoV-2) were measured in 10 organs that SARS-CoV-2 can infect (larynx, trachea, lung, heart, jejunum, ileum, colon, liver, kidney, and testis). Six organs (heart, lung, jejunum, liver, trachea, and ileum) showed changes in the levels of at least one of the proteins. Endurance training increased ACE2 levels in heart (+66.4%), lung (+37.1%), jejunum (+24.7%) and liver (+27.4%), and FURIN in liver (+17.9%) tissue. In contrast, endurance training decreased Neuropilin-1 levels in liver (-39.7%), trachea (-41.2%), and ileum (-39.7%), and TMPRSS2 in lung (-11.3%). Taken together, endurance training altered the levels of host proteins involved in SARS-CoV-2 cell entry in an organ-dependent manner.